A prospective multicenter study of direct comparison of feasibility and safety of pulmonary vein isolation using the minimally interrupted apixaban between second‐generation cryoballoon and radiofrequency ablation of paroxysmal atrial fibrillation: J‐HIT apixaban. Issue 4 (27th June 2020) - Yagishita, Atsuhiko; Goya, Masahiko; Iesaka, Yoshito; Nitta, Junichi; Takahashi, Atsushi; Nagata, Yasutoshi; Hachiya, Hitoshi; Inaba, Osamu; Inamura, Yukihiro; Tanaka, Yasuaki; Watanabe, Keita; Tao, Susumu; et al.
Abstract: Background: The feasibility and safety of pulmonary vein isolation (PVI) using cryoballoon (CB) for paroxysmal atrial fibrillation (PAF) with minimally interrupted apixaban has not fully explored. Methods: In this multicenter, randomized prospective study, we enrolled patients with PAF undergoing CB or radiofrequency (RF) ablation with interrupted (holding 1 dose) apixaban. The primary composite end point consisted of bleeding events, including pericardial effusion and major bleeding requiring blood transfusion, or thromboembolic events at 4 weeks after ablation; secondary end points included early recurrence of AF and procedural duration. Results: A total of 250 patients underwent PVI (125 assigned to the RF ablation and 125 assigned to the CB ablation). The primary end point occurred in 1 patient in the CB ablation group (0.8%; 90% confidence interval [CI], 0.04 to 3.70) and 3 patients in the RF group (2.4%, P = .622; risk ratio, 0333; 90% CI, 0.05 to 2.20). All events were pericardial effusion, all of whom recovered after pericardiocentesis. Early recurrence of AF occurred in 4 patients (3.2%) in the RF group and in 6 patients (4.8%) in the CB group ( P = .749). The procedural duration was shorter in the CB group than that in the RF group (136.5 ± 39.9 vs 179.5 ± 44.8 min, P < .001). Conclusion: CB ablation with minimally interrupted apixaban was feasible and safe in patients with PAF undergoing PVI, which was equivalent to RF ablation. Abstract : Comparison of Safety and Feasibility of Apixaban between Cryoballoon and Radiofrequency pulmonary vein isolation for paroxysmal atrial fibrillation